Study guides

☆☆

Q: 2x - 3y equals 4 and x plus 4y equals -9?

Write your answer...

Submit

Still have questions?

Related questions

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

2x + 4y - 5x + 3y = 7y - 3x

6x plus 4y

10x+2x-3y-4y=12x-7y

If: 2x-3y = -15 and x = 4y Then: x = -12 and y = -3

It is the same as: 6x+4y

4x + 3y - 2x - 7y2x - 4y

The ordered pair is (-1, -2).

3x + 7y

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

4y + 4 = 3y - 5 y = -9

(9,2)

y=2

4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)

Y = 1/2x + 2

(-2, -1)

2x - 3y = -15x => -3y = -17x => -21y = -119x 2x - 3y = 4y => 2x = 7y => 21y = 6x so now you can add the two equations. 0 = -113x x=0 now plug back in 2*0 - 3y = -15*0 -3y = 0 y=0.

2x - 3y = -4x + 4y = -9from the second equation x = -9-4y , substitute it in the first equation.2(-9-4y)- 3y= -4-18-8y-3y = -4-18-11y = -4-11y = -4+18-11y = 14y = -14/11now, solve for x :x = -9-4yx = -9-4(-14/11)x = -43/11

1) 2x + 4y = -62) x -3y = 7We can add 3y to both sides of equation 2) to getx = 3y + 7Now we can substitute 3y + 7 for x in equation 1).In other words, we replace any 'x'es in equation 1) with 3y + 7.2x is two times x, so this becomes 2(3y + 7) which is two times 3y_and_sevenEquation 1) becomes2(3y + 7) + 4y = -6or6y + 14 + 4y = -6or10y + 14 = -6Subtracting 14 from both sides,10y = -20Dividing both sides by 10,y = -2.Substituting -2 for y in equation 1),2x - 8 = -6Add 8 to both sides2x = 2x = 1Check our results with equation 2x - 3y = 71 + 6 = 7

4y + 7 < 3y + 9 4y - 3y < 9 - 7 y < 2

2x+4y = -8 4y = -2x-8 y = -1/2x-2 or y = -0.5x-2

-7y + 4y = -3y

It is a straight line equation.

2x-3y = 4 x+4y = -9 => x = -9-4y Substitute x = -9-4y into the top equation: 2(-9-4y)-3y = 4 -18-8y-3y = 4 -8y-3y = 4+18 -11y = 22 Divide both sides by -11 to find the value of y: y = -2 Substitute the value of y into the original equations to find the value of x: Therefore: x = -1 and y = -2 Remember that the product of a minus times a minus is equal to a plus when working out the original equations,